(untitled) (Cambridge, 2003)
This major volume of original essays traces the role of emotions in human nature through a discussion of the relationship between consciousness and body. It analyzes the importance of emotion for human agency and explores questions of value at the political, ethical and personal levels. Leading researchers reflect on the nature of human feelings; how and why we understand what other people feel, and how our values become involved in such emotions as guilt, fear, shame, amusement, or love.
Keywords: Emotions (Philosophy),Cảm xúc (Triết học)